2021
DOI: 10.1021/acs.biomac.0c01788
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable, Tough, Resilient, and Antifatigue Hydrogels Based on Multiple Hydrogen Bonding Interactions Formed by Phenylalanine Derivatives

Abstract: Noncovalent cross-linked hydrogels with promising mechanical properties are on demand for applications in tissue engineering, flexible electronics, and actuators. However, integrating excellent mechanical properties with facile preparation for the design of hydrogen bond cross-linked hydrogels is still challenging. In this work, an advanced hydrogel was prepared from acrylamide and N-acryloyl phenylalanine by one-pot free-radical copolymerization. Owing to hydrophobicity-assisted multiple hydrogen bonding inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Besides the biochemical properties, their biophysical structure can significantly mediate cell attachment, shape, viability, the differentiation or pluripotency of stem cells, and even tissue repair and regeneration ( Li et al, 2018 ; Cui et al, 2020 ; Yu et al, 2020 ; Yu et al, 2021 ; Zhou et al, 2020 ; Liu et al, 2021 ; Yang et al, 2021a ; Yang et al, 2021b ). Recently, the development of nanofibrous materials has received increasing attention in tissue engineering and regenerative medicine due to their outstanding properties, such as their favorable biological properties, sufficient mechanical strength, highly porous mesh with interconnectivity, extremely high specific surface area, and aspect ratio ( Zhou et al, 2015 ; Zhou et al, 2017 ; Kenry and Lim, 2017 ; Xue et al, 2019 ; Ahmadi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the biochemical properties, their biophysical structure can significantly mediate cell attachment, shape, viability, the differentiation or pluripotency of stem cells, and even tissue repair and regeneration ( Li et al, 2018 ; Cui et al, 2020 ; Yu et al, 2020 ; Yu et al, 2021 ; Zhou et al, 2020 ; Liu et al, 2021 ; Yang et al, 2021a ; Yang et al, 2021b ). Recently, the development of nanofibrous materials has received increasing attention in tissue engineering and regenerative medicine due to their outstanding properties, such as their favorable biological properties, sufficient mechanical strength, highly porous mesh with interconnectivity, extremely high specific surface area, and aspect ratio ( Zhou et al, 2015 ; Zhou et al, 2017 ; Kenry and Lim, 2017 ; Xue et al, 2019 ; Ahmadi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, three bi-carboxyl-included acrylamide monomers, AGLU (glutamic acid derivative), AASP (aspartic acid derivative), and AAMI, were synthesized with minor modifications to the previously described method [ 32 ]. The 1 H NMR spectra shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…As the basic structural unit of proteins, amino acids play a vital role in the formation of the secondary structure of protein through hydrogen bonds. It has been reported that amino acid derivatives, which can form intermolecular multiple hydrogen bond interactions, have the advantage of constructing hydrogels with comprehensive mechanical properties after being introduced into polymer design [ 31 , 32 ]. Owing to the presence of carboxyl groups on amino acids, the resulting hydrogels also present the potential as adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…However, most double network hydrogels are prepared by chemical crosslinking to form three-dimensional networks, leading to the poor self-recovery and fatigue resistance of hydrogels. [16][17][18][19][20] The covalent bond of such hydrogels easily causes irreversible damage when they have large deformations. To address this problem, the most common strategy is to introduce reversible physical bonds (such as hydrogen bonds, [21][22][23] hydrophobic associations, 24,25 ion complexation, 26,27 and polymer chain entanglement 28,29 ) into two networks to synthesize fully physically crosslinked double network hydrogels.…”
Section: Introductionmentioning
confidence: 99%